2015
DOI: 10.1016/j.jagp.2014.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Worsening Cognitive Impairment and Neurodegenerative Pathology Progressively Increase Risk for Delirium

Abstract: BackgroundDelirium is a profound neuropsychiatric disturbance precipitated by acute illness. Although dementia is the major risk factor this has typically been considered a binary quantity (i.e., cognitively impaired versus cognitively normal) with respect to delirium risk. We used humans and mice to address the hypothesis that the severity of underlying neurodegenerative changes and/or cognitive impairment progressively alters delirium risk.MethodsHumans in a population-based longitudinal study, Vantaa 85+, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
97
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 113 publications
(106 citation statements)
references
References 62 publications
(69 reference statements)
4
97
0
2
Order By: Relevance
“…The acute insult triggers acute, transient 81 and fluctuating 87 cognitive deficits during T-maze testing, and further neurodegeneration 78 and acceleration of disease trajectory is observed. 77 Other studies using this model have shown microglia express cyclo-oxygenase (COX) 1 and synthesise prostaglandins.…”
Section: Evidence Linking Delirium and Dementiamentioning
confidence: 99%
See 1 more Smart Citation
“…The acute insult triggers acute, transient 81 and fluctuating 87 cognitive deficits during T-maze testing, and further neurodegeneration 78 and acceleration of disease trajectory is observed. 77 Other studies using this model have shown microglia express cyclo-oxygenase (COX) 1 and synthesise prostaglandins.…”
Section: Evidence Linking Delirium and Dementiamentioning
confidence: 99%
“…88 Inflammation was sufficient, but microglial priming was not essential, for similar deficits reproduced in cholinergic-deficient mice, which could be blocked by donepezil. 80 This suggests an important interplay between acetylcholine deficiency and systematic inflammation but the observation that worsening neurodegeneration makes animals progressively more susceptible to the cognitively disrupting effects of LPS 87 implicates several different neuronal networks.…”
Section: Evidence Linking Delirium and Dementiamentioning
confidence: 99%
“…The evidence that systemic inflammation has more robust effects on the frail or degenerating brain is accumulating in rodent studies (Barrientos et al, 2006, Buchanan et al, 2008, Field et al, 2012, Murray et al, 2012) and this is consistent with inflammatory triggering of human disorders such as delirium, which is a profound and acute cognitive impairment that frequently occurs during acute medical illness or after inflammatory traumas such as orthopedic fracture and surgery (Cunningham and Maclullich, 2013, Inouye et al, 2014). Existing cognitive impairment and neurodegenerative pathology are the key risk factors for delirium incidence and it has been shown that the risk of delirium is proportional to the extent of underlying pathology/baseline cognitive impairment (Davis et al, 2015). It is significant that in this model of acute systemic inflammation TNF-α alone is sufficient to induce acute dysfunction in a cognitive task reliant on attentional and working memory function, two key cognitive domains impaired in delirium.…”
Section: Discussionmentioning
confidence: 99%
“…1,4 Other studies examined delirium at discharge and cognitive change as severity indicators. 22,23 Thus, we chose to examine nine individual measures of delirium episode severity that were classified into four groups of measures requiring: 1) delirium intensity only (based on the 10-item CAM-S long form measurement), 2) delirium intensity and duration, 3) measures requiring information on delirium duration and delirium at discharge, and 4) a measure of cognitive change. We considered two measures that require delirium intensity (peak CAM-S score and mean CAM-S score), along with three measures that require delirium intensity plus delirium duration (sum of all CAM-S scores; sum of all CAM-S scores, only on delirium days; and peak CAM-S score × delirium days).…”
Section: Delirium Assessmentmentioning
confidence: 99%